2018
DOI: 10.1097/ftd.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Survival Time to Biopsy-Proven Acute Rejection and Tacrolimus Adverse Drug Reactions in Pediatric Liver Transplantation

Abstract: Tacrolimus C0 values, its variability, and CYP3A5 polymorphisms were identified as risk factors of AR and tacrolimus ADR. This knowledge may help to control and reduce their incidence in pediatric liver transplant patients. Prospective studies are important to validate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 64 publications
4
14
0
Order By: Relevance
“…The CYP3A5 polymorphism distribution in both donors and recipients included in this study is reported in Supporting Table . The genotype frequencies of the CYP3A5 polymorphism did not deviate from the Hardy‐Weinberg equilibrium ( P > 0.5) . According to the report of the Clinical Pharmacogenetics Implementation Consortium, the estimated allele frequency of CYP3A5*1 and *3 in our population was similar to that reported for the Latin American cohort of patients analyzed in the mentioned guideline.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The CYP3A5 polymorphism distribution in both donors and recipients included in this study is reported in Supporting Table . The genotype frequencies of the CYP3A5 polymorphism did not deviate from the Hardy‐Weinberg equilibrium ( P > 0.5) . According to the report of the Clinical Pharmacogenetics Implementation Consortium, the estimated allele frequency of CYP3A5*1 and *3 in our population was similar to that reported for the Latin American cohort of patients analyzed in the mentioned guideline.…”
Section: Resultssupporting
confidence: 83%
“…The genotype frequencies of the CYP3A5 polymorphism did not deviate from the Hardy-Weinberg equilibrium (P > 0.5). (6) According to the report of the Clinical Pharmacogenetics Implementation Consortium, (34) the estimated allele frequency of CYP3A5*1 and *3 in our population was similar to that reported for the Latin American cohort of patients analyzed in the mentioned guideline. Specifically, our population showed an allele frequency of 25.4% and 74.6% for the CYP3A5*1 and *3 allele, respectively.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations